Contribution of Leg Muscle Power Explosion and Eye-Hand Coordination Against the Smash Ability of the State High School Volleyball Athlete 1 Linggo Sari Baganti - syafruddin syafruddin (Universitas Negeri Padang, 2019)
The problem in this study is the ability to smash the volleyball athletes of SMA Negeri 1 Linggo Sari Baganti not so well. This study aims to determine the contribution of leg muscle explosive power and eye-hand coordination to the volleyball smash ability at SMA Negeri 1 Linggo Sari Baganti. The type of this research is correlational. The population in this research is all male students of class 1 and 2 of SMA Negeri 1 Linggo Sari Baganti. The sampling technique used purposive sampling. Thus the number of samples in this study was 30 people. Data were collected using measurements of all three variables. Leg muscle explosive power variables used a vertical jump test and eye-hand coordination using ball werfen unchanged, while the smash ability used the smash ability test. Data were analyzed with product correlation and followed by multiple correlation. The results showed that the explosive power of the limbs had a significant relationship with the ability to smash because it was found to count 0.576> r table 0.361. Hand-eye coordination has a significant relationship with the ability to smash because it was found to be 0.466 table 0.361. Furthermore, the explosive power of the limbs and eye-hand coordination together have a significant relationship with the ability to smash and are empirically accepted, because it is found that r count = 0.677> r table = 0.361.